Participation in everyday life for young people with chronic pain in Saudi Arabia: “you feel lacking in life and you feel that time is flying by” - Alsaggaf, Fatimah; Coyne, Imelda (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Chronic pain is a common health problem that can have a significant impact on children and young people’s daily life. Although research on pediatric chronic pain has been a priority globally, little is known about young people’s experience of chronic pain in Saudi Arabia. Thus, this article reports on young people’s experience of chronic pain and the impact on their lives in Saudi Arabia which forms part of a larger study. Methods: Multiple case study design following Yin’s (2018) approach was used. Purposeful and theoretical sampling were used to recruit young people aged 12 to 18 who had experienced chronic pain for at least three months, their parents, and their school personnel. Data were collected through in-depth semi-structured face-to-face (n=15) and telephone interviews (n=25) from 40 participants (10 young people, 10 parents, and 20 school personnel). Interviews were recorded, transcribed verbatim, and translated from Arabic to English. Data were analyzed following two phases: 1) constant comparative analysis; and 2) cross-case analysis based on the work of Charmaz and Yin respectively. Findings: Young people’s experiences of chronic pain were categorized into three themes: 1) experiencing chronic pain; 2) impact of pain on quality of life; and 3) everyday strategies to manage chronic pain. All young people reported that their pain was caused by a chronic condition, where the most prevalent pains were musculoskeletal/joint pain, abdominal pain, and headache/migraine. Most young people had encountered challenges with misdiagnosis or delayed diagnosis as to the cause of their chronic pain. They described how their chronic pain interfered with their physical, psychological, and social functioning. They primarily managed their pain with medications and through self-care techniques. The findings also indicated that young people’s generally positive attitude to their pain reflected their beliefs in Allah’s power and the belief that such suffering should be borne according to their Islamic culture. Conclusion: Chronic pain is a significant health phenomenon that tends to restrict the participation of young people in everyday life. However young people used a range of strategies to normalize the pain so that they could continue with their everyday activities like their peers.